Altered Peripersonal Space and the Bodily Self in Schizophrenia: A Virtual Reality Study. (12th April 2021) - Lee, Hyeon-Seung; Hong, Seok-Jin J; Baxter, Tatiana; Scott, Jason; Shenoy, Sunil; Buck, Lauren; Bodenheimer, Bobby; Park, Sohee
Abstract: Self-disturbances such as an anomalous perception of one's own body boundary are central to the phenomenology of schizophrenia (SZ), but measuring the spatial parameters of the hypothesized self–other boundary has proved to be challenging. Peripersonal space (PPS) refers to the immediate zone surrounding the body where the self interacts physically with the environment; the space that corresponds to hypothesized self–other boundary. PPS is represented by enhanced multisensory integration and faster reaction time (RT) for objects near the body. Thus, multisensory RT tasks can be used to estimate self–other boundary. We aimed to quantify PPS in SZ using an immersive virtual reality visuotactile RT paradigm. Twenty-four participants with SZ and 24 demographically matched controls (CO) were asked to detect tactile vibration while watching a ball approaching them, thrown by either a machine (nonsocial condition) or an avatar (social condition). Parameters of PPS were estimated from the midpoint of the spatial range where the tactile RT decreased most rapidly (size) and the gradient of the RT change at this midpoint (slope). Overall, PPS was smaller in participants with SZ compared with CO. PPS slope for participants with SZ was shallower than CO in the social but not in nonsocial condition, indicating an increased uncertainty of self–other boundary across an extended zone in SZ. Social condition also increased false alarms for tactile detection in SZ. Clinical symptoms were not clearly associated with PPS parameters. These findings suggest the context-dependent nature of weakened body boundary in SZ and underscore the importance of reconciliating objective and subjective aspects of self-disturbances.